An analysis of the CAPM for Dhaka Stock Exchange: Evidence from non-financial sector - Hasan, Md Zobaer; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (Global Science and Technology Forum, 2012)
In this study, we examine the Capital Asset Pricing Model (CAPM) structure in Dhaka Stock Exchange (DSE)market for non financial companies. The study also aims at exploring whether the CAPM is applicable in DSE. For this study we have been used monthly stock returns from 60 non-financial companies for the period of January 2005 to December 2009.In order to examine the risk-return trade off in a sample of individual stocks, we apply the usual two stages regression.From the CAPM empirical analysis for individual stocks,it is observed that intercept term is significantly different from zero and slope is not equal to the excess return on the market portfolio.But, the CAPM’s prediction for the intercept is that it should equal zero and the slope should equal the excess returns on the market portfolio. So, the results of the study refute the above hypothesis and offer evidence against the CAPM. Thus, it can be concluded that CAPM is not a suitable indicator of asset prices in Bangladesh over the chosen sample period.The securities market line shows linearity which means that the CAPM linear relationship is enough to express the returns generating process.Moreover, the investors are rewarded for market risk but not for unique risk because unique risk shows insignificancy during the period.